Phytotherapeutic analysis of chloroform-based fractions of Alstonia scholaris and Wrightia tinctoria extracts reveals potent anti-psoriatic activity: an in vitro and in vivo study - Ojha, Madhavi; Manocha, Nilanshu; Kumar, Vinod; Karthikeyan, Ganeshan; Toor, Devinder (MDPI, 2025)
Background/Objectives: Psoriasis, a prevalent dermatological disorder, poses therapeutic challenges due to limited effective treatments or adverse side-effects. Traditional medicinal plants like Alstonia scholaris and Wrightia tinctoria, historically used in Ayurvedic and Siddha practices, show potential in treating inflammatory skin diseases. This study aims to explore their in vitro and in vivo anti-psoriatic properties to develop safer and more effective therapies. Methods: Chloroform:methanol fractions from ethanol extracts of Alstonia scholaris and Wrightia tinctoria were evaluated for anti-psoriatic activity. In vitro assays using HaCaT cells assessed cell viability, apoptosis, and inflammatory markers. In vivo studies utilized an IMQ-induced psoriasis mouse model, evaluating skin lesions, histopathology, and cytokine profiles. Results: Chloroform fractions significantly reduced HaCaT cell viability and induced apoptosis. They also dose-dependently downregulated IL-8 and RANTES levels. In vivo, these fractions reduced skin inflammation, edema, and psoriasis scores. Histopathological analysis showed decreased epidermal thickness and dermal inflammation. Key psoriasis biomarkers IL-17 and IL-23 were significantly reduced. Conclusions: Chloroform:methanol fractions from Alstonia scholaris and Wrightia tinctoria demonstrated potent anti-psoriatic effects in vitro and in vivo. These findings support their potential as novel phytotherapeutic agents for managing psoriasis, offering promise for further development and clinical application.
Keywords: 3214 Pharmacology and Pharmaceutical Sciences; 32 Biomedical and Clinical Sciences; Complementary and Integrative Health; Autoimmune Disease; Psoriasis; 5.1 Pharmaceuticals; Skin; Inflammatory and immune system